2016
DOI: 10.1002/icd.1946
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Predictors of Delay Inhibition in Socioeconomically Disadvantaged Preschoolers

Abstract: This study examined longitudinal associations between specific parenting factors and delay inhibition in socioeconomically disadvantaged preschoolers. At Time 1, parents and 2- to 4-year-old children (mean age = 3.21 years; N = 247) participated in a videotaped parent-child free play session, and children completed delay inhibition tasks (gift delay-wrap, gift delay-bow, and snack delay tasks). Three months later, at Time 2, children completed the same set of tasks. Parental responsiveness was coded from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 78 publications
(105 reference statements)
4
14
0
Order By: Relevance
“…The first main finding was that father autonomy support at age 3 predicted child school readiness at age 5, similar to previous findings regarding the importance of mothers for preschool children’s cognitive development (e.g. Devine et al, 2016; Merz et al, 2015; Razza & Raymond, 2013). Also, the effect of early father autonomy support on later child school readiness was mediated by child language.…”
Section: Discussionsupporting
confidence: 85%
“…The first main finding was that father autonomy support at age 3 predicted child school readiness at age 5, similar to previous findings regarding the importance of mothers for preschool children’s cognitive development (e.g. Devine et al, 2016; Merz et al, 2015; Razza & Raymond, 2013). Also, the effect of early father autonomy support on later child school readiness was mediated by child language.…”
Section: Discussionsupporting
confidence: 85%
“…We expect the modest indirect effects reported via maternal strain to increase in magnitude if additional aspects of family and parental functioning are included. In particular, parenting has been linked to self‐control in multiple samples with effect sizes similar to or in excess of the direct effects found here (Choe et al, ; Merz et al, ), though this has generally not been in a family stress model framework and therefore not always controlled for socioeconomic factors. However, some studies, such as Piotrowski and colleagues' (2013) cross‐sectional survey of parents of children aged 8 months up to 7 years, found parenting characteristics explained approximately 10% of the variance in children's self‐control over and above indicators of SES.…”
Section: Limitationssupporting
confidence: 44%
“…Ideally, across-age comparisons should be made using the same tasks with the same sample. This condition was met in six of the included studies (Gagne & Saudino, 2016;Gaertner, 2012;Lengua et al, 2015;Merz et al, 2016;Miller & Marcovitch, 2015;O'Toole et al, 2018), but as the age range covered in these studies was 2.4 years or less, this provides a rather small window through which to observe age changes in the magnitude of gender differences in delay ability.…”
Section: Discussionmentioning
confidence: 99%
“…The second correlation was that between verbal ability and gender. The data for this correlation were provided in 12 of the included studies Blair et al, 2015;Carlson, Mandell, & Williams, 2004;Carlson & Meltzer, 2008;Carlson, Moses, & Claxton, 2004;Chang et al, 2015;Cuevas et al, 2014;Leve et al, 2013;Merz et al, 2016;Obradovic ´et al, 2016;Peredo et al, 2015;Poland et al, 2016). For these studies, the weighted correlation between verbal ability and gender is found to equal .11, reflecting a small female advantage in verbal ability.…”
Section: Alternative Explanationsmentioning
confidence: 99%